The Convergence of Slobozhanska Iconography in the Discourse of Western European Baroque - Panyok , Tetyanа Volodymyrivna (Eikón / Imago, 2024)
Based on the analysis, generalization and systematization of documents, some well-known to researchers and others not so much investigated, this article studies the influence of Western European Baroque art on the iconography of the region of Slobozhanska (Ukraine) during the 17th and 18th centuries. It is argued that the use of Western European religious themes by Slobozhanshchyna icon painters, in combination with previous iconographic traditions and their transformation to the spiritual and religious features of the region, contributed to the development of a regional iconographic art, a process that could be regarded as a unique phenomenon in the history of Ukrainian culture. As the text will highlight, the stylistic program of Slobozhanshchyna iconography of the Baroque period was influenced by symbolic and emblematic Western European collections that inspired icon painters to create new iconographic subjects. To that aim, the article analyses the artistic and figurative system of iconography, considers its characteristic stylistic features, and draws attention to the borrowing of elements of Western European painting and graphics in Orthodox iconography.